124 - ASSESSMENT OF THE WEIGHT EXCESS AND OBESITY IN ADOLESCENTS WITH THE DOWN'S SYNDROME (Fiep Bulletin - online, 2011)
The objective in this study was to assess the nutritional profile in adolescents with the Down's syndrome and live in the South Region of Tocantins State. They're between 10 and 19 years old. Of them, 7 are male and 11 are female and constitute a Group Census. To instrumentalise the referred assessment the age weight indexes, specific for these people, established by Cronk et al. (1988) were used. And for the dietary assessment a Food Frequency Questionnaire for Adolescents validated by Slater et al. (2003), adapted for the present study was also used. This questionnaire enabled to learn about these adolescents' eating habits in percentage terms related to the food groups that were disposed according to the Adapted Food Pyramid (PHILIPPI, 1999), where the food is distributed in eight groups. It was observed that 44,5% of the adolescents were fat. Of them, 28% were overweight and 16,5% were obese. It was verified that the adolescents' eating habits were inappropriate, since the consumption of vegetables and fruits was lower than the recommended amount in 78% of the adolescents as well as the consumption of milk and dairy products in 50% of these people. It was also observed that all the individuals who compound this study (100%) overeat meat and eggs, and sugar and candies, and 16% of the individuals overeat cereal, bread, tubers and roots. It's concluded that there's a probable relation between the prevalence of weight excess and obesity detected in this study and the inappropriate eating habits found in adolescents. It's advisable to encourage the consumption of healthy food through an awareness and eating reeducation process and this should, in turn, integrate schools, people with the Down's syndrome supporting institutions, families and friends to prevent non-contagious chronic diseases associated with the weight increase and with health complications in adulthood from developing.
Keywords: Nutritional state; adolescents; Down's syndrome